TOSHKENT VILOYATIDA KICHIK BIZNES VA XUSUSIY TADBIRKORLIKNI RIVOJLANTIRISH IMKONIYATLARI - Mullajanov Iskandar Tadjibayevich (MANAGEMENT AND ECONOMICS SCIENTIFIC RESEARCH JOURNAL, 2025)
This article thoroughly examines the share of small business in the Gross Regional Product and its distribution by sector in the Tashkent region. The methodological basis of the research is the methods of theoretical analysis, statistical and economic analysis, and a systematic approach. The following proposals have been developed for the development of small business in the Tashkent region: accelerating the process of transition to a digital economy, forming entrepreneurial clusters in the regions, attracting social segments of the population to entrepreneurship, stimulating innovative and exportoriented activities. The implementation of these measures will contribute to the sustainable development of the region's economy, an increase in jobs, and an improvement in the living standards of the population.